Weight gain or loss after diagnosis and survival outcomes in prostate cancer: a meta-analysis - Feilun Cui; Yueshi Zhang; Xuan Tang; Dandan Gong; Changfeng Man; Yong Shan; Yongjing Zhou; Yu Fan (BMC Cancer)
Abstract Background The relationship between weight changes and survival outcomes in patients with prostate cancer remains inconclusive. This meta-analysis aims to investigate the association between post-diagnosis weight changes and survival outcomes in patients with prostate cancer. Methods We systematically searched for articles indexed in the PubMed, Web of Science, and Embase databases until March 22, 2025. Longitudinal observational studies that examined the association between post-diagnosis weight change and prostate cancer-specific mortality (PCSM) or all-cause mortality among patients with prostate cancer were eligible for inclusion in this analysis. Weight gain and weight loss were defined as either a percentage change from baseline body weight at diagnosis or treatment start, or as an absolute change in kilograms over a specified period. Despite variations in the measured statistical heterogeneity, we employed a random-effects model for all meta-analyses to account for inherent differences in the definitions of weight change. Results Six studies involving 12,269 patients were included in the meta-analysis. When compared to a reference stable weight, post-diagnosis weight gain was associated with an increased risk of all-cause mortality (hazard ratio [HR] 1.23; 95% confidence interval [CI] 1.07–1.42) and PCSM (HR 1.64; 95% CI 1.30–2.07). Conversely, weight loss was linked to an increased risk of all-cause mortality (HR 1.54; 95% CI 1.20–1.97), while no significant association was found between weight loss and PCSM (HR 1.30; 95% CI 0.76–2.22). Begg’s and Egger’s tests indicated no evidence of publication bias. Subgroup analyses revealed that both weight loss (HR 1.38; 95% CI 1.07–1.79) and weight gain (HR 1.25; 95% CI 1.08–1.46) were significantly associated with all-cause mortality when the analysis was restricted to patients with non-metastatic or localized prostate cancer. Conclusions Post-diagnosis weight gain is significantly associated with both all-cause mortality and PCSM in patients with prostate cancer, particularly in those with non-metastatic or localized disease. In contrast, weight loss is primarily linked to an increased risk of all-cause mortality but not to PCSM. However, the observational nature of our data limits our ability to draw definitive conclusions regarding causality.